Modeling and Prediction of Effects of Seafloor Sediment on Sound Velocity Based on Multi-parameter Analysis. Issue 5 (April 2019) - Xiao, Qijun; Luo, Zhonghui; Peng, Bin; Luo, Yongshun; Wang, Min; Liu, Yanghua; Liu, Hanzhang
Abstract: An multi-parameter equation to predict the effects of seafloor sediment on sound velocity is established by means of principal component analysis. The empirical equations in previous reports are analyzed and studied, and calculation errors are also analyzed. The principal component regression model is established based on the data of seafloor sediment of the continental slope in the Southern South China Sea. Theoretical research is performed on the method to eliminate interrelated parameters among the physical parameters affecting the sound velocity and select a f ew independent physical parameters with significant impact on the sound velocity. A three-parameter acoustic speed prediction formula is established with the selected physical parameters, i.e. medium diameter M d (φ), porosity n and plastic limitation Wp of sediment of the continental slope in the Southern South China Sea. Study results show that the minimum relative error of predicted value is -3.77% to 4.48%, which is less than that of the traditional prediction equation.